Peningkatan Hasil Belajar Literasi Numerasi pada Pembelajaran Pendidikan Pancasila melalui Model PBL di Kelas 5 SD Negeri Tambakrejo 01 - Novi, Novi Handayani; Aries Tika Damayanti; Arfilia Wijayanti; Erma Khristiyowati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the learning outcomes of numeracy literacy in Pancasila Education learning through the PBL model in class 5 of Tambakrejo 01 Elementary School, Semarang City. The research method used is classroom action research with 27 students as research subjects. Data were collected through classroom observations and tests. In the pre-cycle, the learning outcomes of students were 55% classical completeness. After going through cycle I, the learning outcomes of students at the classical completeness level were 59%. In cycle II, there was an increase of 70% and in cycle 3, there was a significant increase of 92%. The results showed that 92% of students stated that they had completed the Pancasila Education learning process with the application of the PBL model. The implication of this study is that the Problem Based Learning (PBL) model can effectively improve the learning outcomes of numeracy literacy in the Pancasila Education subject for class 5 students.